Description of two new species of the Lethe manzorum-group (Lepidoptera, Nymphalidae, Satyrinae) from China - Lang, Song-Yun; Monastyrskii, Alexander L. (Zootaxa, 2016)
The Lethe manzorum-group is studied and two new species (L. sisii sp. nov. and L. giancbozanoi sp. nov.) closely related to L. manzorum (Poujade, 1884) from China are described and illustrated.